Sourcing the origins of carnelian in early Chinese civilizations - Meiting Yan; Jiancheng Liu; Chunlei Qin; Xuemei He; Xiaoguang Li; Jian Yu; Ruilin Mao; Hongye Han; Zhanwei Sun; Chong Wang; Zhenbin Xie; Honglin Ran; et al. (Proceedings of the National Academy of Sciences, 2026)
Carnelian beads in high-status burials of the Western Zhou period (ca. 1000–800 BCE) have long been seen as key evidence for long-distance exchange between East Asia and regions to the west, while their geological origins and circulation pathways have remained poorly constrained. Using a newly established geochemical database of 300 geological samples from 27 potential sources across Asia, we conducted trace-element analyses of 11 carnelian beads from the Sanxingdui pits (ca. 1200–1000 BCE), Sichuan Basin, southwest China. Canonical discriminant analysis indicates that the raw materials of these carnelian beads do not primarily derive from south China, but the Yanshan Orogeny, Central Asian Orogenic Belt and some unknown sources that might be close to Hexi Corridor, pointing to raw-material sources located over 1,000 km to the north of the Sichuan Basin. Comparative analyses of contemporaneous beads from Gansu, Shaanxi, and Beijing show similar northern provenance signatures, suggesting a broad and persistent exchange sphere spanning the southern Mongolian Plateau, Loess Plateau, eastern Tibetan Plateau, Central Plains, and Sichuan Basin between 1500–1000 BCE. Our results provide the earliest direct geochemical evidence for long-distance carnelian exchange in Bronze Age China and demonstrate the value of integrating geochemical sourcing with archaeological context to reconstruct ancient interaction networks.